Skip to main content

All Questions

0 votes
1 answer
39 views

How to Prove Division of One Bezier Curve into Two using de Casteljau Algorithm

$\newcommand{\brstbasis}[2]{b^{#1}_{#2}}$ $\newcommand{\posintset}{\mathbb{Z}^{+}}$ $\newcommand{\intset}{\mathbb{Z}}$ $\newcommand{\realset}{\mathbb{R}}$ $\newcommand{\domain}[1]{\operatorname{dom}\...
Ziqi Fan's user avatar
  • 1,840
0 votes
0 answers
28 views

Understanding base cases of inductive proofs in algorithm analysis Cormen et al

I am currently working through Cormen et al's classic book on algorithms and data structures. I am trying to follow an inductive substitution proof that the following time complexity function is $O(n\...
Dan Öz's user avatar
  • 496
0 votes
0 answers
61 views

Mathematical Induction to Prove Binary Search for First Occurrence of an Element in a Sorted Array

$\newcommand{\cardinal}[1]{\abs{#1}}$ $\newcommand{\cardinal}[1]{\abs{#1}}$ $\newcommand{\ceil}[1]{\left\lceil #1 \right\rceil}$ $\newcommand{\floor}[1]{\left\lfloor #1 \right\rfloor}$ $\...
Ziqi Fan's user avatar
  • 1,840
1 vote
1 answer
88 views

How do I write the induction hypothesis when dealing with recursive formulas

The sequence $ \{a_n\}_{n=0}^{\infty} $ is recursively defined by $ a_0 = 0 $, $a_1 = 1 $, $a_2 = 4 $ and $a_n = a_{n-1} + a_{n-3} - n^2 + 8n - 10$ for $ n \geq 3 $. Prove using induction or strong ...
yunolol's user avatar
  • 35
0 votes
1 answer
63 views

How was the solution to this recurrence obtained?

I am trying to understand the solution to the following recurrence. $I(n) = 1+n/B$ if $n \leq \alpha M$ and $I(n) = 4I(n/2)+1$ otherwise. The solution, according to the paper this is from, is $I(n) = ...
user308485's user avatar
  • 1,279
0 votes
1 answer
69 views

Find the explicit formula for this recurrence relation [closed]

Solve this recurrence relation: $$a_0 = 1$$ $$a_n = 2^{2(5-n)+1}* a_{n-1} + 1$$ We've only covered linear homogeneous recurrence relation in our course so I'm a little lost and any help would be ...
Yair Derry's user avatar
0 votes
1 answer
103 views

Proof by induction for java algorithm [closed]

...
Need_MathHelp's user avatar
1 vote
2 answers
494 views

Recurrence equation for $T(n)=T(n-1)+cn$ by substitution (induction)

I was able to solve this relation as described here Solving the recurrence relation $T(n)=T(n-1)+cn$ By the way, my exercises asks also to demostrate by "substitution" and "induction&...
Delayer's user avatar
  • 197
1 vote
2 answers
80 views

Prove $T(n) = T(\lfloor n/2 \rfloor) * T(\lfloor n/2 \rfloor) \leq 2^n$

I am stuck on the below problem. Here is what I have so far, and I have highlighted the area that I am not understanding, particularly in the induction step when we start evaluating for k+1. $T(n) = T(...
c_ab's user avatar
  • 11
-1 votes
1 answer
74 views

Inductive proof for recursive function

Let $\Sigma$ denote an alphabet and $[ \Sigma ]$ set of lists over the alphabet. I've encountered the following function: $f([])=[]$ $f([x])=[x]$, for $x \in \Sigma$ $f(x:L)=f(L)$, for $x \in \Sigma$ ...
Adamat's user avatar
  • 9
1 vote
1 answer
531 views

Proof by Induction on a recursive function

its been a while since I have done proofs and am struggling on a question: Let $T(n)$ be defined recursively as follows: $T(1)=c$ and $T(n)=3T(n/3)+c, \forall n\geqslant 3$, where $c$ is some ...
Ellis Thompson's user avatar
1 vote
1 answer
42 views

Proof of closed-form expression for a recursive formula by induction

With $f:\mathbb{N}\rightarrow\mathbb{R}_+$ and $$T(1)=b$$ $$T(n)=a*T\left(\frac{n}{c}\right)+f(n)$$ for $$a,b,c>0$$ $$n>1$$ Prove by induction that $$T(n)=\sum_{i=0}^k \left(a^i * f\left(\frac{n}...
stackNutzer89's user avatar
2 votes
1 answer
414 views

Proof by induction - algorithm

I need some help to sort out if my answer is right for this question. The algorithm calculates $x^n$. Question: Argue the correctness of the algorithm using proof by induction. Note: Even if you haven'...
TheCoder's user avatar
0 votes
1 answer
83 views

Tips for a recursive function, proof by induction

Suppose the following $$ f(0)= 0$$ $$ f(1)=2$$ $$ f(n)= 4f(n-1)-3f(n-2)$$ I want to prove that $$f(n)= 3^n -1$$ by induction. I started by trying this $$f(n+1)=4f(n)-3f(n-1)$$ Which gives me this: $$ ...
amk123abc's user avatar
0 votes
2 answers
70 views

Can somebody help me with this mathematical induction proof? [closed]

It's a recursive equation and I'm not sure how to demonstrate it through mathematical induction.
Natalia's user avatar
  • 15

15 30 50 per page